High-weather-resistant plated anti-yellowing crystal glass and preparation method thereof
By alternately depositing low-refractive-index and high-refractive-index layers on the surface of a glass substrate to form a multilayer composite dielectric film, the problem of discoloration of the glass substrate under ultraviolet light is solved, and high weather resistance and long lifespan of coated anti-yellowing color-changing crystal glass are achieved.
Patent Information
- Application Number
- CN202610342384.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-19
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-03-19
AI Technical Summary
Existing glass substrates and their surface ink coatings are prone to irreversible discoloration under ultraviolet light, affecting aesthetics and user experience.
A multilayer composite dielectric film is formed by alternately depositing low-refractive-index layers and high-refractive-index layers on the surface of a glass substrate using a magnetron sputtering process. The odd-numbered layers are low-refractive-index layers, and the even-numbered layers are high-refractive-index layers. The specific materials are silicon dioxide and zinc oxide or titanium dioxide. The total number of layers is odd, and the thickness is 50-100nm.
It effectively reduces ultraviolet light penetration, slows down the discoloration of glass and ink, ensures the yellowing resistance of glass components, maintains a 25-year service life, and maintains high visible light transmittance and low reflectivity.
Smart Images

Figure CN122212496B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass panel manufacturing technology, specifically to a highly weather-resistant coated anti-yellowing crystal glass and its manufacturing method. Background Technology
[0002] In existing technologies, under the long-term influence of external light, especially ultraviolet light, the glass substrate and its surface ink coating undergo a slow photochemical degradation reaction, leading to changes in the material's molecular structure and manifesting macroscopically as an irreversible "discoloration" phenomenon. Conventionally used soda-lime ultra-clear glass and soda-lime ordinary clear glass exhibit significant discoloration, particularly white products which show the most pronounced yellowing, affecting the overall aesthetic design and user experience.
[0003] In view of this, it is necessary to design a highly weather-resistant coated anti-yellowing crystal glass to solve the above problems. Summary of the Invention
[0004] In view of the technical problems existing in the background art, this application provides a high weather-resistant coated anti-yellowing crystal glass and its preparation method. The preparation method uses a magnetron sputtering process to alternately deposit a low refractive index layer and a high refractive index layer on the surface of a glass substrate to obtain a high weather-resistant coated anti-yellowing crystal glass.
[0005] In a first aspect, embodiments of this application provide a method for preparing highly weather-resistant coated anti-yellowing crystalline glass, comprising the following steps: S1, Clean the glass substrate and dry it for later use; S2, the glass substrate is cleaned using plasma and bombarded with Ar plasma before entering the cavity; subsequently, a low-refractive-index layer and a high-refractive-index layer are alternately deposited on the surface of the glass substrate using magnetron sputtering to form a multilayer composite dielectric film, thus obtaining a high-weather-resistant coated anti-yellowing crystal glass; wherein, the total number of layers of the multilayer composite dielectric film is an odd number greater than or equal to 5, the odd-numbered layers are low-refractive-index layers, and the even-numbered layers are high-refractive-index layers; the low-refractive-index layer is a silicon dioxide layer, and the high-refractive-index layer is a zinc oxide layer or a titanium dioxide layer.
[0006] Furthermore, the middle odd-numbered layer is the nth layer, and the high-refractive-index layers symmetrically arranged on both sides of the nth layer are made of different materials.
[0007] Furthermore, the refractive index of the low-refractive-index layer is 1.46.
[0008] Furthermore, the zinc oxide layer has a refractive index of 1.9, and the titanium dioxide layer has a refractive index of 2.5.
[0009] Furthermore, the thickness of the single-layer low-refractive-index layer and the high-refractive-index layer is 15±5nm.
[0010] Furthermore, the multilayer composite dielectric film has a total of 5 layers, which are silicon dioxide layer, titanium dioxide layer, silicon dioxide layer, zinc oxide layer, and silicon dioxide layer in sequence.
[0011] Furthermore, the total thickness of the multilayer composite dielectric film is 50-100 nm.
[0012] Furthermore, when depositing the silicon dioxide layer, a silicon-aluminum target is used, and the deposition rate is controlled at 5-10 nm / min; when depositing the zinc dioxide layer, a zinc oxide ceramic target is used, and the deposition rate is controlled at 8-15 nm / min; when depositing the titanium dioxide layer, a titanium oxide ceramic target is used, and the deposition rate is controlled at 4-8 nm / min.
[0013] Secondly, embodiments of this application provide a high weather-resistant coated anti-yellowing crystal glass, which is prepared using the aforementioned preparation method and includes a glass substrate, a low refractive index layer and a high refractive index layer alternately stacked from the front side of the glass substrate upwards; the high weather-resistant coated anti-yellowing crystal glass has an ultraviolet transmittance of 62-68%, a visible light transmittance of 85-93%, a visible light reflectance of 3-10%, and a color difference value ΔE ≤ 1.5 before and after coating.
[0014] The beneficial effects of this invention are: (1) The method for preparing the high weather-resistant coated anti-yellowing crystal glass of the present invention employs a magnetron sputtering coating process to alternately deposit low-refractive-index layers and high-refractive-index layers on the surface of a glass substrate, forming a multilayer composite dielectric film structure; wherein the total number of low-refractive-index layers and high-refractive-index layers is odd, with odd-numbered layers being low-refractive-index layers and even-numbered layers being high-refractive-index layers. This configuration, under the absorption, reflection, and destructive interference effects of the coating layers in the multilayer composite dielectric film structure, reduces the amount of transmitted ultraviolet light, thereby slowing down the discoloration of the glass and ink, enhancing the overall anti-yellowing ability of the panel, and ensuring a 25-year service life for the glass assembly.
[0015] (2) The ultraviolet transmittance of the high weather resistance coated anti-yellowing crystal glass of the present invention is 62-68%, the visible light transmittance is 85-93%, the visible light reflectance is 3-10%, and the color difference value before and after coating is ΔE≤1.5.
[0016] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0018] Figure 1 This is a schematic diagram of a 5-layer multilayer composite dielectric membrane structure in an embodiment of this application.
[0019] Figure 2 This is a schematic diagram of the light transmission trajectory when using the high weather resistance coated anti-yellowing crystal glass of this application.
[0020] Figure 3 The results are from the ultraviolet irradiation test of Comparative Example 1.
[0021] Figure 4 This is a comparison chart of the ultraviolet irradiation test results of Example 1 and Comparative Example 2.
[0022] Figure 5 This is a comparison chart of the ultraviolet irradiation test results of Example 1 and Comparative Example 3.
[0023] Figure 6 This is a comparison chart of the ultraviolet irradiation test results of Example 1 and Comparative Example 4. Detailed Implementation
[0024] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0026] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0027] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0028] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0029] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces). Those skilled in the art can understand the specific meaning of the above terms in the embodiments of this application according to the specific circumstances.
[0030] In existing technologies, sodium-calcium ultrawhite and sodium-calcium ordinary white, which are commonly used in the home appliance industry, will exhibit obvious discoloration. The yellowing phenomenon is most obvious in white products, which affects the overall aesthetics of the product.
[0031] The method for preparing high weather-resistant coated anti-yellowing crystalline glass provided in this application embodiment employs a magnetron sputtering coating process to alternately deposit low-refractive-index layers and high-refractive-index layers on the surface of a glass substrate, forming a multilayer composite dielectric film structure. The total number of low-refractive-index and high-refractive-index layers is odd, with odd-numbered layers being low-refractive-index layers and even-numbered layers being high-refractive-index layers. This configuration, through the absorption, reflection, and destructive interference of the coating layers in the multilayer composite dielectric film structure, reduces the amount of transmitted ultraviolet light, thereby mitigating the discoloration phenomenon of the glass / ink.
[0032] The method for preparing high weather-resistant coated anti-yellowing crystal glass provided in this application includes the following steps: S1, Clean the glass substrate and dry it for later use; S2, the glass substrate is cleaned using plasma and bombarded with Ar plasma before entering the cavity; subsequently, a low-refractive-index layer and a high-refractive-index layer are alternately deposited on the surface of the glass substrate using magnetron sputtering to form a multilayer composite dielectric film, thus obtaining a high-weather-resistant coated anti-yellowing crystal glass; wherein, the total number of layers of the multilayer composite dielectric film is an odd number greater than or equal to 5, the odd-numbered layers are low-refractive-index layers, and the even-numbered layers are high-refractive-index layers; the low-refractive-index layer is a silicon dioxide layer, and the high-refractive-index layer is a zinc oxide layer or a titanium dioxide layer.
[0033] The middle odd-numbered layer is defined as the nth layer, and the high-refractive-index layers symmetrically arranged on both sides of the nth layer are made of different materials.
[0034] The refractive index of the low-refractive-index layer is 1.46. The refractive index of the zinc oxide layer is 1.9, and the refractive index of the titanium dioxide layer is 2.5.
[0035] The thickness of the single-layer low-refractive-index layer and the high-refractive-index layer is 15±5nm.
[0036] The total thickness of the multilayer composite dielectric film is 50-100 nm.
[0037] In some embodiments, the multilayer composite dielectric film has a total of 5 layers, which are silicon dioxide layer, titanium dioxide layer, silicon dioxide layer, zinc oxide layer and silicon dioxide layer in sequence.
[0038] When depositing a silicon dioxide layer, a silicon-aluminum target is used, and the deposition rate is controlled at 5-10 nm / min; when depositing a zinc dioxide layer, a zinc oxide ceramic target is used, and the deposition rate is controlled at 8-15 nm / min; when depositing a titanium dioxide layer, a titanium oxide ceramic target is used, and the deposition rate is controlled at 4-8 nm / min.
[0039] The high weather-resistant coated anti-yellowing crystal glass provided in this application has an ultraviolet transmittance of 62-68%, a visible light transmittance of 85-93%, a visible light reflectance of 3-10%, and a color difference value ΔE ≤ 1.5 before and after coating.
[0040] Example 1 Please see Figures 1 to 2 As shown, this embodiment provides a method for preparing highly weather-resistant coated anti-yellowing crystal glass, including the following steps: S1. Clean the soda-lime glass substrate using a wafer washer. The wafer washer requires pure water and the water temperature is set to 35°C. After cleaning, dry the substrate.
[0041] S2, Glass surface pretreatment: The soda-lime glass substrate is cleaned with plasma to remove dirt, grease and oxides from the surface. Before entering the cavity, it is bombarded with Ar plasma at a power of 500W for about 3 minutes to increase surface activity.
[0042] Subsequently, a coating process is performed on the soda-lime glass substrate using a coating equipment: by using a magnetron sputtering target, ions react with oxygen in the cavity to deposit, and a silicon dioxide layer, a titanium dioxide layer, a silicon dioxide layer, a zinc oxide layer, and a silicon dioxide layer are sequentially deposited on the surface of the soda-lime glass substrate to obtain a highly weather-resistant coated anti-yellowing crystal glass.
[0043] The thickness of the single-layer film is controlled at 15±5nm.
[0044] The process parameters for the coating treatment are as follows: The targets used are silicon-aluminum targets, titanium dioxide ceramic targets, and zinc oxide ceramic targets, which are used for magnetron sputtering to generate silicon dioxide layers, titanium dioxide layers, and zinc oxide layers, respectively.
[0045] Magnetron sputtering requires the preparation of argon (sputtering gas), oxygen (reacting gas), helium (auxiliary gas), etc.
[0046] Background vacuum: 3.0 × 10 -3 Pa, to ensure the membrane layer is pure and free of contamination.
[0047] Sputtering power: power density 4-6 W / cm³ 2 This is to ensure that the film layer is uniform and stable.
[0048] Sputtering temperature: 180±20℃, to enhance the activity of the glass surface.
[0049] Please see Figure 2 As shown, the high weather resistance coated anti-yellowing crystal glass obtained in this application includes a glass substrate 10 and a multilayer composite dielectric film 20 deposited on the front side of the glass substrate 10.
[0050] In practical use, the incident light is absorbed, reflected, and interfered with by the multilayer composite dielectric film 20, which reduces the amount of ultraviolet light that passes through. This slows down UV penetration, thereby mitigating the discoloration of the glass substrate 10 and the ink layer 30 on the back of the glass substrate 10.
[0051] The optical performance test results of the three samples prepared in Example 1 are shown in Table 1 below.
[0052] Table 1 As shown in the table above, the ultraviolet transmittance of the high weather-resistant coated anti-yellowing crystal glass is 65.9%, the visible light transmittance is 89.9%, and the visible light reflectance is 6.9%. This scheme maintains high visible light transmittance while ensuring a certain degree of ultraviolet protection, with a color difference ΔE < 1.5 before and after coating.
[0053] Comparative Example 1 The difference compared to Example 1 is that the thickness of the single-layer coating was adjusted to 10±5 nm. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0054] The optical performance test results of the three samples prepared in Comparative Example 1 are shown in Table 2 below.
[0055] Table 2 As shown in the table above, the ultraviolet transmittance is 71.8%, the visible light transmittance is 90.7%, and the visible light reflectance is 5.2%. This solution increases the visible light transmittance of the substrate by reducing the film thickness, and the color difference value ΔE before and after coating is less than 1.5, but at the same time, its ultraviolet blocking effect is reduced.
[0056] Comparative Example 2 Compared with Example 1, the difference is that the thickness of the single-layer coating was adjusted to 20±5nm. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0057] The optical performance test results of the three samples prepared in Comparative Example 2 are shown in Table 3 below.
[0058] Table 3 As shown in the table above, the ultraviolet transmittance is 60.6%, the visible light transmittance is 85.1%, and the visible light reflectance is 8.5%. This scheme enhances the ultraviolet blocking rate by increasing the film thickness, while reducing the visible light transmittance. The color difference value ΔE before and after coating is greater than 1.5.
[0059] Comparative Example 3 Compared with Example 1, the difference is that the zinc oxide layer is replaced with a titanium dioxide layer, that is, the high refractive index layer uses a single material; the multilayer composite dielectric film consists of a silicon dioxide layer, a titanium dioxide layer, a silicon dioxide layer, a titanium dioxide layer, and a silicon dioxide layer in sequence; the rest is roughly the same as in Example 1, and will not be repeated here.
[0060] The optical performance test results of the three samples prepared in Comparative Example 3 are shown in Table 4 below.
[0061] Table 4 As shown in the table above, the ultraviolet transmittance is 61.8%, the visible light transmittance is 86.2%, and the visible light reflectance is 8.5%. This scheme affects the interference effect by changing the high-refractive-index layer material, resulting in a color difference ΔE > 1.5 before and after coating.
[0062] Comparative Example 4 Compared with Example 1, the difference is that the titanium dioxide layer is replaced with the zinc oxide layer, that is, the high refractive index layer uses a single material; the multilayer composite dielectric film consists of a silicon dioxide layer, a zinc oxide layer, a silicon dioxide layer, a zinc oxide layer, and a silicon dioxide layer in sequence; the rest is roughly the same as in Example 1, and will not be repeated here.
[0063] The optical performance test results of the three samples prepared in Comparative Example 4 are shown in Table 5 below.
[0064] Table 5 As shown in the table above, the ultraviolet transmittance is 68.9%, the visible light transmittance is 87.3%, and the visible light reflectance is 8.6%. This scheme affects the interference effect by changing the high-refractive-index layer material, resulting in a color difference ΔE > 1.5 before and after coating.
[0065] The optical performance of Example 1 and Comparative Examples 1-4 is summarized in Table 6.
[0066] Table 6 Comparing Example 1 with Comparative Example 1, it can be seen that reducing the film thickness will lead to a decrease in the ultraviolet blocking effect, but at the same time, the visible light transmission will increase slightly.
[0067] Comparing Example 1 and Comparative Example 2, it can be seen that increasing the film thickness will lead to an increase in the ultraviolet blocking effect, but at the same time, the visible light transmission will be significantly reduced.
[0068] Comparing Example 1 with Comparative Examples 3 and 4, it can be seen that changing the high refractive index material will greatly enhance the blocking effect of ultraviolet light, but at the same time, it will also significantly reduce the transmission of visible light, and the interference phenomenon will be more obvious.
[0069] The high weather-resistant coated anti-yellowing crystal glass prepared in Example 1 and Comparative Examples 1-4 was tested for relevant properties. The specific test items, test methods and test results are as follows.
[0070] UV aging resistance test and requirements: Use a 1000W UV lamp. 3. With a main peak wavelength of 365nm and a lamp distance of 450mm from the sample, after irradiation for 6 hours, the color difference value ΔE ≤ 1.5.
[0071] Adhesion cross-cut adhesion test and requirements: Draw a 10×10 grid with a spacing of 1 mm on the part, apply SCOTCHMAG1G TAPT810 (3M) tape to it, and then lift it vertically upwards quickly three times. There should be no peeling.
[0072] Abrasion resistance test and requirements: The friction head is wrapped with non-woven fabric and subjected to a 500g load. After 5000 cycles, the film layer does not peel off and the fogging is ≤3%.
[0073] Temperature and humidity resistance test requirements: 65℃, 95% humidity, for 168 hours. No discoloration, peeling, or cracking should occur after the test, and the optical performance degradation should be ≤3%.
[0074] Visual inspection: White enamel was printed on the back of the glass panels prepared in Examples 1 and 1-4 using 103 white ink and a 150-mesh screen. Ultraviolet irradiation tests were then conducted after printing. The test results are as follows: Figures 3 to 6 As shown.
[0075] The experiment showed that after the UV irradiation test in Comparative Example 1, there was a significant color difference between the detected area and the undetected area, and a noticeable color change occurred. The color difference value ΔE was greater than 1.5, which did not meet the performance index requirements.
[0076] Examples 1, 2, 3, and 4 showed no significant color change after UV irradiation tests, and the color difference between the irradiated and unirradiated areas was less than 1.5, meeting the performance requirements.
[0077] The comparison shows that the optical interference phenomenon in Comparative Examples 2, 3, and 4 is serious, which fails to highlight the original color of the glaze. Compared with the untreated original pieces, △E>1.5, which does not meet the appearance index requirements.
[0078] That is, in Example 1, the color difference values before and after coating and before and after ultraviolet irradiation are both less than 1.5, which meets all performance and appearance indicators and satisfies the usage requirements.
[0079] Comparative Example 1 failed the UV aging resistance test; Comparative Examples 2, 3, and 4 failed the appearance inspection, showing obvious yellowing, with △E>1.5.
[0080] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for preparing a highly weather-resistant coated anti-yellowing crystalline glass, characterized in that, Includes the following steps: S1, Clean the glass substrate and dry it for later use; S2, the glass substrate is cleaned with plasma and bombarded with Ar plasma before entering the cavity; Subsequently, a low-refractive-index layer and a high-refractive-index layer are alternately deposited on the surface of the glass substrate using magnetron sputtering to form a multilayer composite dielectric film, thereby obtaining a high-weather-resistant coated anti-yellowing crystal glass. The multilayer composite dielectric film has a total of 5 layers, which are silicon dioxide layer, titanium dioxide layer, silicon dioxide layer, zinc oxide layer, and silicon dioxide layer in sequence. The thickness of a single low-refractive-index layer is 15±5nm, and the thickness of a single high-refractive-index layer is 15±5nm.
2. The method for preparing high weather-resistant coated anti-yellowing crystal glass according to claim 1, characterized in that, The refractive index of the low-refractive-index layer is 1.
46.
3. The method for preparing high weather-resistant coated anti-yellowing crystal glass according to claim 1, characterized in that, The zinc oxide layer has a refractive index of 1.9, and the titanium dioxide layer has a refractive index of 2.
5.
4. The method for preparing high weather-resistant coated anti-yellowing crystal glass according to claim 1, characterized in that, The total thickness of the multilayer composite dielectric film is 50-100 nm.
5. The method for preparing high weather-resistant coated anti-yellowing crystal glass according to claim 1, characterized in that, When depositing a silicon dioxide layer, a silicon-aluminum target is used, and the deposition rate is controlled at 5-10 nm / min; when depositing a zinc oxide layer, a zinc oxide ceramic target is used, and the deposition rate is controlled at 8-15 nm / min; when depositing a titanium dioxide layer, a titanium oxide ceramic target is used, and the deposition rate is controlled at 4-8 nm / min.
6. A highly weather-resistant coated anti-yellowing crystal glass, characterized in that, The high weather-resistant coated anti-yellowing crystal glass is prepared by the preparation method of any one of claims 1 to 5, comprising a glass substrate, a low refractive index layer and a high refractive index layer alternately stacked from the front side of the glass substrate upwards; the high weather-resistant coated anti-yellowing crystal glass has an ultraviolet transmittance of 62-68%, a visible light transmittance of 85-93%, a visible light reflectance of 3-10%, and a color difference value ΔE ≤ 1.5 before and after coating.
Citation Information
Patent Citations
Low-reflection coating glass
CN110248906A
Coating with photo-induced hydrophilicity
EP1291331A2
